UniSZA’s Muhammad Anas received Highest Student Leadership Award - UMP, PNC (Pejabat Naib Canselor, 2016)
Muhammad Anas Misbahudin of Universiti Sultan Zainal Abidin (UniSZA) was announced as the recipient of Higher Education Ministry’s highest student leadership award at ‘Anugerah Tokoh Siswa’ held in Universiti Malaysia Pahang (UMP) Gambang campus on April 23, 2016.